Utilization Of RRI Bandar Lampung Podcast As Hobby And Lifestyle Information Media (Descriptive Study Of RRI Digital Application) - Wibowo, Panji Prasttyo (Journal of Public Relations and Digital Communication (JPRDC), 2025)
Podcasts are the right means of entertainment for most Indonesians when utilizing leisure time, as well as the people of Bandar Lampung who make this one of the activities that become their reference, namely listening to podcast broadcasts produced by the Public Broadcasting Corporation of Radio Republik Indonesia Bandar Lampung. Podcasts were created as a means of media publication in the field of information where this is certainly a consumption material that is of interest to the public. LPP RRI Bandar Lampung produces podcasts in collaboration with its broadcasting sector, namely PRO 2 with the 92.5 FM radio broadcast channel with the tagline Your Best Friend, then the youtube platform with an account called Pro 2 RRI Bandar Lampung, while the official platform launched by RRI National is called the RRI Digital application. Based on the results of observations, research interviews conducted, most of the people of Bandar Lampung are interested in listening to podcasts, namely through YouTube podcasts with the concept of Interview Podcasts with the most popular themes being hobbies and lifestyles. Due to the high public interest in RRI Bandar Lampung's youtube podcasts, the production of podcasts that are only broadcast once a month 1 to 2 times and there are gaps from the podcast team itself which can finally be found by the community is a matter of criticism for the community or loyal listeners of RRI Bandar Lampung. It is recommended that RRI Bandar Lampung can increase the podcast broadcast schedule and creative ideas that are raised so as not to lose viewers and can increase public interest in listening to podcast broadcasts.